Respiratory outcomes among plant processing workers in Durban, South Africa. Issue 3 (3rd July 2022) - Shezi, Busisiwe; Mathee, Angela; Alfers, Laura; Dobson, Richard; Ndlovu, Patrick; Reddy, Tarylee; Street, Renee A.
Abstract : Plant products used by informal traditional medicine traders go through various methods of manual processing to yield a final single or multi-concoction product; however, the prevalence of potentially associated respiratory outcomes has yet to be established. The aim of this study was to describe respiratory outcomes associated with processing plants among informal traditional medicine traders. Questionnaires related to the preparation of plant products and respiratory outcomes were administered to study participants by trained researchers. Of the 216 traders, nocturnal cough, nasal allergies and waking with a feeling of tightness in the chest were the most frequently cited respiratory outcomes (43, 35 and 22%, respectively). The study highlighted the burden of respiratory outcomes among traders who process plant products and the need for targeted workplace interventions.